Family Food Insecurity, Food Acquisition, and Eating Behavior Over 6 Months Into the COVID-19 Pandemic - Hollis-Hansen, Kelseanna; Ferrante, Mackenzie J.; Goldsmith, Juliana; Anzman-Frasca, Stephanie (Journal of nutrition education and behavior, 2022)
Describe coronavirus disease 2019 (COVID-19)-related employment and food acquisition changes for food-secure and food-insecure households. Examine associations between food insecurity, parent food acquisition, and child eating. A nationally representative cross-sectional survey with parents (N = 1,000) in Fall 2020. Measures included sociodemographics, food retail regulations, food insecurity, frequency of meals, changes in parent employment, food preparation, and food acquisition because of COVID-19. Parents that reported recent food insecurity were more likely to report COVID-19-related employment changes (eg, job loss, reduced hours) and food acquisition changes. Food insecurity was modestly associated with more frequent in-person restaurant dining (B = 0.12, t(999) = 4.02, P < 0.001), more frequent restaurant delivery (B = 0.13, t(999) = 4.30, P < 0.001), less frequent homecooked meals (B = −0.14, t(999) = 4.56, P < 0.001) but was not associated with take-out (B = 0.02, t(999) = 0.62, P = 0.54). Food insecurity was associated with employment changes, parent food acquisition, and children's consumption of homecooked and restaurant meals during COVID-19. Future work could explore resources that help parents acquire affordable, nutritious food.